18 'devicectomy' following severe nickel allergy after transcatheter closure of an atrial septal defect with amplatzer septal occluder. (2nd February 2018) - Fernandes, P; Michielon, G; Fraisse, A
Abstract : Background: Transcatheter device closure of secundum atrial septal defects (ASD) using Amplatzer Septal Occluder (ASO) is usually well tolerated with favourable outcome with analgesics. Case: 10 years old boy underwent successful transcather device closure of secundum ASD in august 2011 with a 22 mm Amplatzer Septal Occluder device. Three days after the procedure he developed severe migraines. These were debilitating headaches resulting in loss of school days and poor quality of life. He was found to have grade 1 reaction to nickel allergy following skin test. He received extensive medical therapy for migraine over a period of 6 years under neurology team with no improvement in symptoms. After several discussions, we decided to surgically remove the device and close the ASD. This was accomplished under bypass surgery. Postoperative course was uneventful. Immediately the next day after successful removal of the device and closure of the defect, his headaches were completely resolved. Intraoperatively it was found that even after 6 years the device had not endothelialized and there was exposure of blood to the uncovered device. Discussion: Nickel allergy to ASO device have previously been reported. However, these are short lived migraine headaches up to 6 months or chest pain responsive to medical therapy. Our case is first to describe the long-term Nickel allergy to ASD device containing ninitol in children requiring surgical removal of device. Conclusion: History of nickel allergy should be explored prior to device closure of ASD. In case of know allergy alternative devices or surgical repair should be considered.